An innovative procedure for introducing the lean concept into the internal drug supply chain of a hospital. Issue 6 (8th October 2018) - Regattieri, Alberto; Bartolini, Alessandro; Cima, Maddalena; Fanti, Maria Giulia; Lauritano, Diego
Abstract : Purpose: In a hospital, the management of different materials (i.e. waste, drugs, equipment, etc.) is fundamental from an economical point of view and also when considering its impact on patient treatment. The purpose of this paper is to introduce by an innovative approach lean principles in the management of this supply chain. Design/methodology/approach: After the contextualization of the importance of the drug management in hospitals, authors analyze the literature in particular discussing the points of weakness. They propose an innovative methodology to implement a lean principle in this particular supply chain. After a general discussion authors discuss the application of the proposed methodology in the largest Italian hospital, the Policlinico Sant'Orsola – Malpighi in Bologna. Findings: The results are very encouraging, confirm the value of the methods and motivate the authors to do further research. The proposed methodology takes into account both a technical approach and the real behavior of a hospital including logistics knowledge and motivation for material management in ward personnel. Real results are interesting both in term of economic impact and in term of effect on patient care. Originality/value: Maximizing patient care is the mission of the healthcare system; however, poor management of drugs and materials can have serious effects on the quality of service. In the last years, several excellent technological solutions have been developed, but often their application in the field was limited and ineffective due to the gap in knowledge and commitment required and available in the ward's personnel. The new methodology developed is focused to solve this gap and was tested in an important case study.